2016
DOI: 10.1515/cclm-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

High homocysteine and low folate plasma concentrations are associated with cardiovascular events but not bleeding during warfarin treatment

Abstract: In patients receiving warfarin treatment, high homocysteine and low folate plasma concentrations are associated with increased risk for cardiovascular events but not major bleeding. For homocysteine levels, there is also an association with all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Hcy can modulate periodontal diseases by increasing acute‐phase reactant proteins in the circulation, through IL‐6, TNF‐α and/or regulated and normal t‐cell expressed and secreted (RANTES) release from the inflamed tissues (Polepalle, Moogala, Boggarapu, Pesala, & Palagi, 2015; Sun, Wang, Zhang, Zeng, & Wang, 2005). Hcy levels elevate in case of vitamin B 12 or FA deficiency (Dillon et al, 2010; Lind, Jansson, Nilsson, & Johansson, 2016). Wang et al (2005) showed positive contribution of low‐dose FA on hyperhomocysteinaemia by inhibiting chemokine secretion from monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Hcy can modulate periodontal diseases by increasing acute‐phase reactant proteins in the circulation, through IL‐6, TNF‐α and/or regulated and normal t‐cell expressed and secreted (RANTES) release from the inflamed tissues (Polepalle, Moogala, Boggarapu, Pesala, & Palagi, 2015; Sun, Wang, Zhang, Zeng, & Wang, 2005). Hcy levels elevate in case of vitamin B 12 or FA deficiency (Dillon et al, 2010; Lind, Jansson, Nilsson, & Johansson, 2016). Wang et al (2005) showed positive contribution of low‐dose FA on hyperhomocysteinaemia by inhibiting chemokine secretion from monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies also showed a similar reduction in folate levels under FD treatment [32][33][34][35] . Importantly, low folate levels have been linked with the risk for certain tumors 36 .…”
Section: Discussionmentioning
confidence: 99%
“…No association of serum folate levels with bleeding. In a longitudinal cohort human study on 719 patients taking long-term warfarin, high homocysteine levels (≥17.2 µmol/L) and serum folate (≥11.9 nmol/L) were not associated with bleeding events, but both were associated with cardiovascular events (myocardial infarction, ischemic stroke, peripheral arterial emboli) [288] (Table 2).…”
Section: Folate (B9)mentioning
confidence: 99%